TWO NEW GENERA OF DAPRIDAE (PROCTOTRUPOIDEA : HYMENOPTERA) FROM INDIA - RAJMOHANA, K.; NARENDRAN, T.C. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2000)
Two new genera of Diapriidae, viz. Alareka and Vadana are described with type species A. keralensis and V. sholayarica respectively. A key to genera of Indian Diapriinae based on males is also provided. Abbreviations : AV-Anterior view, DV-Dorsal view, FW-Forewing. F1-Fl1=Flagellomeres, HB-Head width, HL-Head length, L.B-Length-breadth ratio, m=Marginal vein, OD-Ocellar diameter, OOL-Ocelocular length, POL-Post ocellar length; sm-Submarginal vein; SFStigmal vein; T2=2" Metasomal tergite. TSS-Trans scutellar suture.